Norming studies for lexicosemantic and affective characteristics of European Portuguese words: A literature review - Félix, Sara B. (2021)
Words are widely used as stimuli in cognitive and linguistic research. As words may vary on various domains (e.g., lexicosemantic and affective), which can influence performance in many ways, it is essential to select them carefully. However, databases of European Portuguese words are still relatively scarce, and their presentation is spread in various sources. The aims of this work were: (1) to provide a review of the databases containing information on lexicosemantic, affective, and free association norming data for European Portuguese words published since the year 2000; (2) to summarize the definitions of the different variables; and (3) to combine in a single database the norming data available at this point. We found 25 databases with 18 containing lexicosemantic and affective norming data and seven containing word free association norms. These databases include words from various categories (e.g., nouns and adjectives), characterized on different variables (e.g., familiarity, imagery, valence, age of acquisition and animacy). This review provides a useful tool for researchers looking for Portuguese word-related resources. A thorough review of the databases, including some details about each one, is presented. The combined database is shared with the scientific community via the Open Science Framework: https://osf.io/9ta3y/.